2016
DOI: 10.1055/s-0042-119686
|View full text |Cite
|
Sign up to set email alerts
|

Increase in FLAIR Signal of the Fluid Within the Resection Cavity as Early Recurrence Marker: Also Valid for Brain Metastases?

Abstract: Results 3 of 6 cases with local tumor recurrence showed a FLAIR signal increase (sensitivity 50.0 %, specificity 100.0 %). In one case, this sign was observed even about 3 months before tumor recurrence.The specificity of FLAIR signal increase for overall tumor recurrence (local and distant) was also 100.0 %, but with a lower sensitivity of 13.0 %.Quantitative analysis showed significant differences for signal intensity of the resection cavity as well as for the change of signal intensity of the resection cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Similar findings have been reported by others (Zakaria et al, 2014). High FLAIR signal in the resection cavity in postoperative patients may indicate impending local recurrence after neurosurgical resection (Bette et al, 2016a). Conversely, neither pretreatment CBV (Essig et al, 2003) nor MRS is predictive of response to radiosurgery (Chernov et al, 2007).…”
Section: Predicting Response Prior To Treatment Initiation (Prognostimentioning
confidence: 99%
“…Similar findings have been reported by others (Zakaria et al, 2014). High FLAIR signal in the resection cavity in postoperative patients may indicate impending local recurrence after neurosurgical resection (Bette et al, 2016a). Conversely, neither pretreatment CBV (Essig et al, 2003) nor MRS is predictive of response to radiosurgery (Chernov et al, 2007).…”
Section: Predicting Response Prior To Treatment Initiation (Prognostimentioning
confidence: 99%
“…29,30,34,35,40,42 Other MRI techniques such as postcontrast T1-w and FLAIR can help to assess the response to treatment or the recurrence of BMs from BC. [33][34][35] Some MRI techniques such as DTI and rsfMRI can help to evaluate the cognitive impairment or the functional connectivity of BMs from BC. 29,32,36 MRI findings of BMs from BC can vary depending on the BC subtype, such as HER2-positive, luminal or triplenegative.…”
Section: Discussionmentioning
confidence: 99%
“…Some MRI techniques such as CE MRI, DWI, ADC, DSC and SWI can help to differentiate BMs from BC from other brain tumours such as GBM or ischemic lesions 29,30,34,35,40,42 . Other MRI techniques such as postcontrast T1‐w and FLAIR can help to assess the response to treatment or the recurrence of BMs from BC 33–35 . Some MRI techniques such as DTI and rsfMRI can help to evaluate the cognitive impairment or the functional connectivity of BMs from BC 29,32,36 …”
Section: Discussionmentioning
confidence: 99%
“…The result could be due to the hyperemic response of the margins that occurs 48 h after surgery. Both Bette et al and Forsyth et al identified an increase in reactive CE in the hours following surgery, indicative of a hypervascular response [ 25 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%